The Effect of Marketing Mix on Consumer Purchase Interest - Elfa Fitria Anabila; Ihwan Susila (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Batik cloth has spread throughout Indonesia and each region has its own characteristics. One of the cities in Blora Regency, Cepu, is a small city that produces the largest petroleum on the island of Java. From this wealth, batik motifs typical of the region were created, one example of which is oil refinery batik. The Blora batik motif is inspired by the resources available in the region. The aim of this research is to analyze the influence of the marketing mix on consumer buying interest (study of Surya Mustika Cepu Batik consumers). The research method in this study uses a quantitative research method. The data source for this research is primary data, namely data obtained directly from respondents. The data collection method uses a questionnaire via Google Form. The population in this research is all consumers of Batik Surya Mustika. The sampling technique in this research is non-probability sampling. The sample used in this research was 107 respondents. This research uses SMARTPLS 3.0 software. This research uses Structural Equation Model (SEM) analysis with Partial Least Square (PLS). The results of this research are that products do not have a significant effect on purchase interest. Price does not have a significant effect on Purchase Intention. Distribution does not have a significant effect on Purchase Interest. Promotion has a significant effect on Purchase Interest and has a positive direction. People who influence Buying Interest and have a positive direction. Physical evidence influences buying interest and has a positive direction. The process does not have a significant effect on buying interest.